THE IMPORTANCE OF SUPPLIER EVALUATION IN SHORT SUPPLY CHAINS - GÁBORNÉ SZŰCS, Beáta Pató; KISS, Fanni (Studia Universitatis Babeș-Bolyai Oeconomica, 2019)
The consideration of supply chains can foster the viability and maintainability of local producers. The formation and retention of the market may be complicated for local producers; therefore it is advisable to take the creation of supply chains into consideration. Constant feedback and evaluation is highly important to maintain successfully operating short supply chains and supplier evaluation forms could act as the starting point of these chains. These forms reflect the strengths and weaknesses of suppliers, based on which the correction of mistakes can be done and the performance of suppliers may be enhanced. The aim of this study is to examine the role of supplier evaluation form and relationships between customers and suppliers in short supply chains, from a local producer’s point of view through a case study. The scientific relevance of this study is to draw particular attention to short supply chains which are and will be of high importance considering local economies. As the case study reveals, it is recommended for the members of short supply chains to use supplier evaluation forms. JEL classification: Q31;